Architectural Forms and Distribution Characteristics of Beacon Towers of the Ming Great Wall in Qinghai Province - Wenwu Chen; Yumin Du; Kai Cui; Xianglong Fu; Shuya Gong (Journal of Asian Architecture and Building Engineering, 2017)
Through consulting literature discussing the specific military function of beacon towers, this paper classified the architectural forms of 116 beacon towers of the Ming Great Wall in Qinghai province, and determined their distribution characteristics. According to related documents, their architectural forms can be divided into six types based on the relationship between their stage body and circumjacent buildings (the moat, enclosing wall and small flint) with spotty and linear distribution features. To further explain the linear distribution characteristics, the concept of a beacon tower link was used to illustrate the military intelligence routes and transmission orientation of the intelligence system of the Xining Guarding Post during the Ming Dynasty. By researching the change rule of the beacon tower elevations situated on such links, the authors found that most of these elevations have decreasing trends along their military intelligence orientation. In addition, beacon tower links closely surround the Xining Guarding Post with a radial shape, and they follow some important river systems and ancient roads. Many links follow the rule that beacon tower elevations can change suddenly at the corners where they are located, which reflects the wisdom of ancient Chinese architectural design.